Commentary: Whither the epigenetics of child psychopathology? Some reflections provoked by Barker et al. (2018). (25th March 2018) - Sonuga‐Barke, Edmund J.S.; Fearon, Pasco
Abstract : Barker et al.'s. (2018 ) review addresses one of the most fundamental questions in the fields of child psychology and psychiatry – How can adverse experiences shape development to a sufficient degree and in profound and enduring ways to create long term risk for later mental disorder and disability? In particular they discuss the plausibility of differential methylation as an epigenetic mechanism by which such exposures can become neuro‐biologically embedded. Our commentary rises six question relating to key issues that need to be addressed as we search for definitive evidence from human studies that such mechanisms actually do make an important causal contribution to abnormal trajectories of development to disorder. Abstract : Read the full article at doi: 10.1111/jcpp.12782